Augustine through the ages an encyclopedia - Fitzgerald, Allan D.; Cavadini, John; Djuth, Marianne; O'Donnell, James J.; Van Fleteren, Frederick (Grand Rapids, MI Eerdmans, 1999)
Includes bibliographical references and index.
Keywords: Augustine, Saint, Bishop of Hippo -- encyclopedias